Shunt‐blocking layers for semitransparent perovskite solar cells - Hörantner, MT; Nayak, PK; Mukhopadhyay, S; Wojciechowski, K; Beck, C; McMeekin, D; Kamino, B; Eperon, GE; Snaith, HJ (Wiley, 2016)
Perovskite solar cells have shown phenomenal progress and have great potential to be manufactured as low‐cost large area modules. However, perovskite films often suffer from pinholes and the resulting contact between hole‐ and electron transporting layers provides lower resistance (shunt) pathways, leading to decreased open‐circuit voltage and fill factor. This problem is even more severe in large area cells and especially in the case of neutral color semitransparent cells, where a large absorber‐free area is required to provide the desired transparency. Herein, a simple, inexpensive, and scalable wet chemical method is presented to block these “shunting paths” via deposition of transparent, insulating molecular layers, which preferentially bind to the uncovered surface of the electron collecting oxide, without hindering charge extraction from the perovskite to the charge collection layers. It is shown that this method improves the performance in semitransparent cells, where the enhancement in open‐circuit voltage is up to 30% without negatively impacting the photocurrent. Using this method, we achieved an efficiency of 6.1% for a neutral color semitransparent perovskite cell with 38% average visible transmittance. This simple shunt blocking technique has applications in improving the yield as well as efficiency of large area perovskite solar cells and light emitting devices.